Reconstruction of economic issues and challenges of the Mughals during the reign of Aurangzeb (1658-1707) - Abul Hassan Ashari, Mohamad Zulfazdlee; Ahmad Safian, Nursafira; Jamsari, Ezad Azraai (Morse Florse, 2022)
The economy was a crucial backbone in the governance of the Mughal Empire. Nevertheless, it was also an issue afflicting the stability of the empire due to the various challenges faced by its rulers during their reign, including the era of Aurangzeb (1658-1707). Military operations directed by Aurangzeb, especially to Deccan, were blamed to be the sole factor of economic crisis which happened during the period of his time. Consequent to the economic problem, Aurangzeb was forced to introduce a few appropriate measures to ensure the empire’s economic stability to secure the sustainability of the Mughals dominance. Based on these, this article has the objective of re-examining the economic issues and challenges of the Mughals during the era of Aurangzeb’s reign. In addition to that, this article also attempts to carry out a reconstruction of the economic problems in order to understand them which needed to be dealt with by Aurangzeb. This study applies a qualitative approach via historical study and content analysis of data while accumulating and analysing them based on primary and secondary sources. Results of this study showed that military expeditions during the era of Aurangzeb was collectively not the lone factor to the economic downturn of the Mughal kingdom. In fact, the economic challenges which needed to be tackled by Aurangzeb had already been in existence prior to his ascension to the throne. The economic challenges were inherited by Aurangzeb from previous administration causing him to undertake several measures to handle the economic problems in order to ensure sustainability of the empire also encompass the economic aspect, an important core to the stability of any government. The systems of jagir and mansabdar which were closely linked to economic and military progress of the Mughals serve as a proof to its competence in managing its fiscal policies. The economy is an important core to the building of any state or nation. Not only do economic and financial strengths invigorate the stability of a government but they also serve as a major resource to development and governance. Because of that the Mughal Empire placed a heavy emphasis on the Indian economy by introducing a number of measures and policies with regards to its administration such as in the tax collection system and the military hierarchy system known as mansabdar (Jaffar, 1972). Nevertheless, every ruler of the Mughal Empire faced economic problems during their reigns. For example, during the era of Shah Jahan, many government officials lived on debts due to the kingdom’s failure to pay their salary (Edwardes & Garrett, 1930). Aurangzeb’s regime (1658-1707) was considered a successful and dominant rule in the history of the Mughals. According to Sarkar (1962), the Mughal Empire went through a golden age with its dominion being the largest in the history of the Mughals, covering from Ghaznah to Chatgaon and Kashmir to Karnatak. In addition to this, Aurangzeb also carried out reforms through strengthening of the Mughal’s administrative institutions. These were driven by his own desire to see his government is administered according to the mould of Islamic rule. Moreover, the grip of the ulema faction within the Mughal kingdom after Aurangzeb’s ascension to the throne also contributed to the reformations (Haq, 1977; Ashari, 2021; Ashari et al. 2021). Nonetheless, Aurangzeb was not free from economic problems when he was at the helm of the empire. Qamaruddin (2004) stated that Aurangzeb inherited the kingdom from Shah Jahan’s rulership which was in debt. This posed a difficulty to Aurangzeb to improve the situation as it was beyond his control. Meanwhile, Richards (2008) suggested that it was Aurangzeb’s military campaigns to the Deccan province that spelt disaster to the Mughal economy. Even though the Mughals military expeditions finally took control of the province, demands by the aristocrats of Deccan for mansab from Aurangzeb inflicted economic instability due to limited resources. This view of Richards portrayed that economic challenges of the Mughals at that time were caused by its policies and political measure and not linked to the issue of debts inherited from the previous administration. Based on such views, this article has the objective of re-examining the issue of Mughal’s economic challenges during the reign of Aurangzeb (1658-1707). This article also intends to carry out a reconstruction of the issue in understanding and remapping the issue of economic problems which Aurangzeb had to deal with. This study employed a qualitative method via historical study and content analysis in gathering and analysing data based on primary and secondary sources.